Toward Healthier Cookie Habits: Assessing the Role of Packaging Visual Appearance in the Expectations for Dietary Cookies in Digital Environments - Reinoso-Carvalho, Felipe; Campo, Raffaele; De Luca, Modesto; Velasco, Carlos (Frontiers in Psychology, 2021)
As we tend to consume more and more via e-commerce platforms, the digital version of a dietary product’s package can be one of the most important touchpoints that the consumer has with such product during the purchasing stage of the consumer’s journey. Hence, a dietary food/drink properly presented via its packaging in e-commerce is key, for example, to nudge consumers towards healthier purchase habits. In this study, we assessed the role of different configurations of visual cues commonly present in a packaging (jar vs bag, transparent vs opaque, labeled vs unlabeled) in the expectations for dietary cookies when presented in a digital environment. Here, a between-participants study was conducted where eight different packages with different combinations of the three aforementioned features were digitally evaluated by the participants. The results suggest that the presence (vs absence) of labeling triggered the highest ratings on most assessed dimensions (product quality, healthiness, lightness, sweetness, crumbliness, price, tastiness, greediness for product, product/packaging liking). Moreover, transparent (vs opaque) packaging tends to yield higher expectations concerning this product´s quality (i.e., product liking, package liking, greediness), having an opposite effect on the expected healthiness for such cookies. Some particular interactions between these three visual cues are also being discussed as part of the obtained results. In summary, our results point to how the visual appearance of packaging can be strategically configured in order to potentially nudge consumers towards healthier cookie purchase habits.